2018
DOI: 10.1002/jcp.27332
|View full text |Cite
|
Sign up to set email alerts
|

DL‐3‐n‐butylphthalide alleviates vascular cognitive impairment by regulating endoplasmic reticulum stress and the Shh/Ptch1 signaling‐pathway in rats

Abstract: Background DL‐3‐n‐butylphthalide (NBP) has been approved to be effective in improving cognitive deficits. The aim of the current study was to determine whether NBP protects against cognitive deficits in a rat model of vascular dementia (VD) induced by chronic cerebral hypoperfusion (CCH) by regulating the sonic hedgehog (Shh)/patched1 (Ptch1) pathway and endoplasmic reticulum stress (ERS)‐related markers. Methods Adult male Sprague‐Dawley rats were subjected to permanent bilateral occlusion of the common carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In fact, in a neuronal model of VD low concentrations of copper potentiate zinc-induced ER stress pathways 68 . Moreover, DL-3-n-butylphthalide was www.nature.com/scientificreports/ shown to protect against cognitive deficits in a rat model of VD by regulating ER stress-related markers 69 . This work highlights a new conceptual model for AD and PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a neuronal model of VD low concentrations of copper potentiate zinc-induced ER stress pathways 68 . Moreover, DL-3-n-butylphthalide was www.nature.com/scientificreports/ shown to protect against cognitive deficits in a rat model of VD by regulating ER stress-related markers 69 . This work highlights a new conceptual model for AD and PD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it shows neuroprotective effects in AD (Wang et al, 2016), PD (Xiong et al, 2012), neurotoxicity (Zhao et al, 2016), traumatic brain injury (Zhao et al, 2017), and spinal cord injury (He et al, 2017). NBP is protective against cognitive impairment induced by CCH by increasing sonic hedgehog/patched 1 pathway markers and decreasing endoplasmic reticulum stress-related markers (Niu et al, 2018), or activating the AKT/Nrf2 pathway in the hippocampus of rats (Qi et al, 2018). Our previous work has revealed that NBP can quickly accelerate a recovery in CBF and improvements in cognitive function (Xiong et al, 2017; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that NBP exerts multi‐target protective effects against ischemic stroke, including reducing oxidative stress, inhibiting inflammatory responses, alleviating neuronal apoptosis, ameliorating BBB damage, and increasing regional blood flow . Moreover, emerging evidence indicates that NBP also have beneficial effects on cognitive function of Alzheimer's Disease (AD) and vascular dementia, through regulating endoplasmic stress, reducing neuronal apoptosis, and glial reactivity …”
Section: Introductionmentioning
confidence: 99%